Students’ Perspective of Online Learning on Speaking Class during Covid-19 Pandemic - Fitriani, Yustina; Bandung, Murti; Kadri, Mohtana Kharisma (LPPM Universitas Bumigora Mataram, 2020)
All educational institutions during COVID-19 pandemic move to online learning to prevent the spread of this virus. All students and lecturers of the institutions have no other option. They must use some of online platforms to continue the learning process. The aim of this research was to know the students’ perspective of online learning on speaking class during COVID-19 pandemic. This research was categorized as mixed method research. There were 20 items of the questioner that have been distributed. The result showed that 14 items disagree and 6 items agree.